Analytical toolset to characterize polyurethanes after exposure to artificial weathering under systematically varied moisture conditions. (September 2019) - Scholz, P.; Wachtendorf, V.; Elert, A.-M.; Falkenhagen, J.; Becker, R.; Hoffmann, K.; Resch-Genger, U.; Tschiche, H.; Reinsch, S.; Weidner, S.
Abstract: Polyether and -ester urethanes (PU) were exposed to artificial weathering at 40 °C and artificial UV radiation in a weathering chamber. In 3 parallel exposures, humidity was varied between dry, humid, and wet conditions. Material alteration was investigated by various analytical techniques like size exclusion chromatography (SEC), liquid chromatography-infrared spectroscopy (LC-FTIR), thermal-desorption gas chromatography-mass spectrometry (TD-GC-MS), fluorescence mapping and dynamic mechanical analysis (DMA). Our results show that depending on the weathering conditions, different degradation effects can be observed. By means of SEC an initial strong decrease of the molar masses and a broadening of the mass distributions was found. After a material dependent time span this was followed by a plateau where molar mass changes were less significant. A minor moisture-dependent degradation effect was only found for polyester PU. Fluorescence measurements on two materials revealed an increase in the luminescence intensity upon weathering process reaching a saturation level after about 500 h. The changes in the optical properties observed after different exposure conditions and times were very similar. The TD-GC-MS data showed the fate of the stabilizers and antioxidant in the course of weathering. LC-FTIR measurements revealed a change in peak intensities and the ratio of urethane and carbonyl bands. Highlights: Broad range of analytical techniques monitoring changes of the polymer, of lower mass degradation products and of additives. Systematic study focusing on the variation of moisture conditions during weathering. Combination of chromatographic and spectroscopic methods focusing on both molecular, optical and macroscopic changes. Initial crosslinking followed by molecular weight degradation was found. Results show an accelerated degradation at humid or wet conditions especially of polyester PU.